Pedestrian flow Characteristics and Level of Service Assessment for Footpaths along the section of Koshi Highway, at Biratnagar - Dahal, Sahil (International Journal on Engineering Technology and Infrastructure Development, 2024)
Pedestrians are considered to be one of the vulnerable road users in regards to road safety. Biratnagar stands as one of Nepal's bustling cities with several ongoing road development project. Being one of the busiest city, activities of the city should be supported by adequate facilities, such as pedestrian facilities— crucial yet much neglected matters, so pedestrians can walk along the roadway. As a result, conflicts between pedestrians with motor vehicle users and accidents might occur at any time. This study was aimed at investigating the geometric conditions of pedestrian facilities, identifying the characteristics of pedestrians and the pedestrian facilities and determining the level of service for pedestrian facilities at three junctions of Koshi Highway. The study was conducted through survey of location, survey of geometric conditions, estimation of the number of pedestrians using sidewalk (data recorded every 15 minutes), measurement of pedestrian speed, and questionnaire about pedestrian’s identity, destination, as well as travel time and distance. Data analysis was carried out to identify the pedestrian characteristics, pedestrian flow characteristics, and pedestrian level of service. The obtained data were then analyzed using INDO HCM 2017 in order to find out the level of service and it was found the sidewalk at those junctions has PLOS of grade “A” and further the project also included the qualitative assessment for analysis of geometric condition of pedestrian facilities.